Women and Marriage: An Analysis Comparativ Literature on The Novel Indonesia, England, and America - Syahril Syahril (Ar-Raniry: International Journal of Islamic Studies, 2017)
A novel can represent reality. Thus, a character in a novel with his or her complexitymight be a portrait or a representation of a real person. This article discusses representations or images of women in three novels from three different social backgrounds. They are Kalau Tak Untung (Selasih, Indonesia), Far From The MaddingCrowd (Thomas Hardy, England), and The Great Gatsby (F. Scott Fitzgerald, UnitedStates). All of these three novels represent women in both positive and negative images.The positive images are: independent, hard working, rebellious, and futuristic (in thinking). Meanwhile, the negative images are reckless, naïve, materialistic, seductive,unfaithful, egoist, and passive. The three novels show some facts. The first is that womenwill work hard when they are in an unpleasant situation, particularly when they needmoney. In this situation, they will not mind doing a man’s job. The second similarity isthat woman with good education seems to have better behavior than those who lackeducation. The third fact is that there are some women who value their happiness by thewealth they can get.